Pembuatan Direktori Perpustakaan Sekolah Selingkungan Kota Padang Panjang Provinsi Sumatera Baratng Provinsi Sumatera Barat - Monalita, Poppy; Rahmah, Elva (Ilmu Informasi Perpustakaan dan Kearsipan, 2016)
This paper discussed of the School Library Directory about Padang Panjang the province of West Sumatra. The preparation of this directory aims to create a product that can help users easily find information relating to school libraries around the town of Padang Panjang. In this paper the discussed about creation directory the school library around the town of Padang Panjang the province of West Sumatra. Methods used in writing this paper is the method descriptive. Technique data collection who writers included is direct observation, interview, direct observation, and the literature study. Based on the discussion we can conclude that measures in the manufacture of directory of the school library around Padang Panjang the province of west sumatra following; first, collected data on the school library around Padang Panjang; second, sorts data obtained; third, make a directory of the school library around Padang Panjang; the fourth, make a design of the cover.Keyword: Directory, Padang Panjang, school library.